The Impact Of Green Brand Image Implementation And Legal Compliance On Customer Loyalty At MSME Grama Sphere Medan - Chantika Mayzira; Adelina Lubis; Ikbar Pratama; Rizkan Zulyadi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the influence of Green Brand Image and Legal Compliance in Business on Consumer Loyalty in MSMEs Grama Sphere Medan. In an era of increasing consumer awareness of sustainability issues and the importance of legal compliance, these two factors are considered to play an important role in shaping consumer trust and loyalty. This study uses a quantitative approach with an associative method, involving 80 respondents who have made at least two purchases at Grama Sphere. The data collection technique was carried out through a questionnaire with a Likert scale, and data analysis was carried out using multiple linear regression in SPSS 27. The results of the study indicate that both partially and simultaneously, Green Brand Image and Legal Compliance have a positive and significant effect on Consumer Loyalty. The coefficient of determination (R²) value of 60.8% indicates that the independent variables are able to explain variations in consumer loyalty substantially. The implications of these findings suggest that MSMEs need to strengthen their environmentally friendly brand image and maintain legal compliance as a strategy in building long-term loyalty. This study contributes to the local literature on sustainable marketing and ethical and legal-based business practices.